Malignant Pelvic Solitary Fibrous Tumor: Histologic and Immunohistochemical Features of a Rare Case with Literature Review - Chen, Weiwei; Paczos, Tamera; Chen, Frank (North American Journal of Medicine and Science, 2013)
Solitary fibrous tumor (SFT) is a rare mesenchymal neoplasm. First described as a pleural lesion, SFTs have been reported in extra-thoracic sites as well. SFT arising in the pelvis is extremely rare, and its malignant form is even rarer. Here we report a case of malignant pelvic SFT with analysis of its histologic and immunohistochemical features. Clinically, the tumor was slow-growing and remained unchanged in size for six years. However, a sudden increase in size by 2 cm occurred within a few months. Gross examination of the surgically excised tumor showed a well-encapsulated tan white mass. Microscopically, the tumor was composed of interlacing bundles of spindle cells with focal high cellularity, moderate cytologic atypia and a mitotic count up to 12/10 HPF. Scattered collagen bundles and staghorn blood vessels were noted. Immunostains revealed that the tumor cells were strongly positive for CD34, CD99, Bcl-2 and vimentin, and negative for smooth muscle actin, muscle specific actin, pancytokeratin, S100, CD117, CD68 and calretinin. Ki67 stain indicated a very high proliferation index. These features are consistent with malignant SFT. Malignant SFTs have a much worse prognosis compared with its benign counterpart, and hence it is important to recognize this entity. We emphasize that histologic features, such as increased mitotic activity, high cellularity and nuclear pleomorphism, as well as a panel of immunohistochemical stains, especially CD34 and CD99, are invaluable in the diagnosis of malignant SFT.